Targeted therapy and drug resistance in triple-negative breast cancer: the EGFR axis. (20th April 2020) - Lev, Sima
Abstract : Targeting of estrogen receptor is commonly used as a first-line treatment for hormone-positive breast cancer patients, and is considered as a keystone of systemic cancer therapy. Likewise, HER2-targeted therapy significantly improved the survival of HER2-positive breast cancer patients, indicating that targeted therapy is a powerful therapeutic strategy for breast cancer. However, for triple-negative breast cancer (TNBC), an aggressive breast cancer subtype, there are no clinically approved targeted therapies, and thus, an urgent need to identify potent, highly effective therapeutic targets. In this mini-review, we describe general strategies to inhibit tumor growth by targeted therapies and briefly discuss emerging resistance mechanisms. Particularly, we focus on therapeutic targets for TNBC and discuss combination therapies targeting the epidermal growth factor receptor (EGFR) and associated resistance mechanisms.